Recreating the Banana Grower: The Role of Private Certification Systems in the Windward Islands Banana Industry - Haakon Aasprong (Culture Unbound: Journal of Current Cultural Research, 2012)
Private standards and certification schemes in agrifood networks tend to be de-scribed as neoliberal, suggesting that they share a common understanding of that which they seek to govern and the tools to be used. Although such certification systems do have many features in common, this article argues that much is to be learned by contrasting certification systems with regard to their ideational ground-ings. Through a historically grounded discussion of the adoption and implementa-tion of two certification systems – GLOBALGAP and Fairtrade – in the Wind-ward Islands banana industry, it is argued that there are important differences with regard to how the systems envision shared key concepts such as accountability, adaptability, professionalism and not least sustainability. These differences permeate the standards as well as their enforcement structures, demonstrating a flexibility in certification as governmental technology which is often overlooked. Moreover, the article explores how the certification systems’ governmental rationalities articulate with local understandings of the role of farmers and agriculture in the Windward Islands, arguing that the tension existing between the visions embedded in the systems mirrors a tension within these islands societies. This tension preceded the adoption of the certification systems and continues to influence their implementation today.